(untitled) (Bangladesh Journal of Animal Science, 2025)
The survey was conducted based on structured questionnaires in four districts viz. Dhaka, Bogura, Mymensingh, and Panchagarh) from 9 May to 8 June, 2024 to assess different milk and dairy products produced in selected sweetmeat shops, quantity of milk utilized in production, and the consumer preferences regarding sweetmeats in those districts. The study was conducted to depict Bangladesh’s traditional and modern sweetmeat, milk and dairy products to a wider audience by emphasizing their local names. Survey data were analyzed using Microsoft Excel to determine milk requirements per product, production of sweetmeats and doi, and sweetmeat sales per day in those selected districts. Milk sourcing trends revealed that all surveyed shops in Dhaka, Bogura, Mymensingh, and Panchagarh relied entirely on other dairy farms. The trend of regular milk consumption was found highest in the Dhaka which was more than double of the Mymensingh district. We found only cow milk in the consumer’s drinking glass. Only 57% of the respondents in Panchagarh made some dairy products at home which was 83 – 100% in three other districts. There were no digestion issues related to milk and dairy products in Dhaka and Bogura. In total we have identified 68 dairy products in sweetmeat shops of those four districts and majority of the products are chhana based. Some products were found very similar, varied only by a tiny modification in the manufacturing process. The expensive milk and/or dairy products were Creamjam, Lengcha, Japanibhog and Kheersha found in Bogura and each of the item priced BDT 700/Kg. The expensive dairy products found in Dhaka was Madraji Golla priced BDT 680/Kg. The manufacturers in Bogura obtained more regulatory certificates and least was in Dhaka and Panchagarh. The findings in the present study indicates the importance of similar studies in the other districts to make complete national data domain on diversity of traditional dairy products, consumer preferences for them and their price variation. Bangladesh Journal of Animal Science 54(1): 20-35, 2025